Aussi vite que possible… - Antoine Hennion (Ateliers d'Anthropologie)
Virtuosity is at the heart of musical performance, but it has an ambivalent status. It is both the acme of art, and a dangerous temptation. Drawing on a comparison between different genres, I would like to suggest that beyond the classical opposition between body, entertainment, collective trance music, on a side, and written music that focuses on the composition of a work and is largely developed by opposing virtuoso seduction, on the other, it is possible to give virtuosity its ability to express a musical truth by turning it into an aesthetic of performance: less a technical feat than a necessary positioning of the work in the fragility of a present that is always to be recovered.